Accurate characterization method of coal pore and pore throat structure of different coal ranks based on two-dimensional NMR liquid nitrogen fracturing cycles. (1st June 2023) - Qin, Lei; Zhang, Xian; Matsushima, Jun; Zhou, Bin; Liu, Peng; Wang, Ruizhe; Lin, Siheng
Highlights: Accurate characterization of pore structure of different coal ranks using 2D NMR. Characterize the pore throat characteristics of different coal ranks. Analyze T1 -T2 spectra and 3D peak map to obtain the development of coal pores. Abstract: In order to accurately characterize the porosity and pore throat structure of different coal grades under liquid nitrogen fracturing cycles, this paper tests the T2 and T1 -T2 sequences of different grades of coal samples (lignite, bituminous coal and anthracite) before and after the fracturing cycles. The results show that the total pore space of A, L and B is arranged in descending order according to the initial state. The internal porous throat distribution of lignite and anthracite coal samples is wider. With the increase of the number of fracturing cycles, the internal pore space of the three coal grade coal samples has been improved, of which lignite has the largest lifting rate; The internal porous throat distribution of L coal samples was reduced by 0.97%. The internal pore space of B and A coal samples increased by 34.62% and 6.33%, respectively, the pore-throat distribution increased by 28.96% and 16.98%, respectively.